Death and the “possible” Exchange. Beyond Jean Baudrillard - Esteban Ortega, Joaquín (Revista de Filosofía, 2022)
The present work, in dialogue with the reflection of Jean Baudrillard, attempts to reconsider ontologically the non-being, so that the hollowness of the simulacrum does not proclaim itself to be more real than the real because, since nothingness has been expropriated and emptied, the exchange of world and of life with it is impossible. Only a tragic thought, animated by the agonizing energy of its contradiction, can rethink the reversibility of life and death.